Pekerja Anak Perempuan di Wilayah Pedesaan Adat; Dilematika Keadilan Gender - Nikodemus Niko (Raheema, 2019)
In the traditional society, children who work in domestic sector is obligations were able to be refuted. So that in a rural area which still exists in the customs, sometimes we can found many girls who work at home (domestic sector) and in the field as voluntarily. It is regarded as “children obligation” to help their parents. This research focuses on Desa Cowet, Balai Sub-District, District Sanggau West Kalimantan, in which methods used is the qualitative descriptive approach. The data used was primary data which obtained through technique interview and observation, and secondary data was sourced from the book, scientific journal, and relevant sources. The traditions of community assume that girls required to work in the domestic sector. It is regarded as an obligation to do as the female. Girls help their mother at home or in the fields and rubber. The division of labor based on gender, the female has work more within households. So, girls who work to help their mother will inherit the same work with undertaken by their mother. The construction that girls will inherit a capital work, their perception should be converted.